Synthesis and characterization of hybrid molecularly imprinted polymer (MIP) membranes for removal of methylene blue (MB) - Asman, Saliza; Yusof, Nor Azah; Abdullah, Abdul Halim; Haron, Md. Jelas (MDPI, 2012)
This work reports the synthesis and characterization of a hybrid molecularly imprinted polymer (MIP) membrane for removal of methylene blue (MB) in an aqueous environment. MB-MIP powders were hybridized into a polymer membrane (cellulose acetate (CA) and polysulfone (PSf)) after it was ground and sieved (using 90 µm sieve). MB-MIP membranes were prepared using a phase inversion process. The MB-MIP membranes were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Parameters investigated for the removal of MB by using membrane MB-MIP include pH, effect of time, concentration of MB, and selectivity studies. Maximum sorption of MB by PSf-MB-MIP membranes and CA-MB-MIP membranes occurred at pH 10 and pH 12, respectively. The kinetic study showed that the sorption of MB by MB-MIP membranes (PSf-MB-MIP and CA-MB-MIP) followed a pseudo-second-order-model and the MB sorption isotherm can be described by a Freundlich isotherm model.